1999
DOI: 10.1002/pen.11557
|View full text |Cite
|
Sign up to set email alerts
|

In‐situ reactive blending of polyethylene and polypropylene in co‐rotating and counter‐rotating extruders

Abstract: Blends of high-density polyethylene (HDPE) and polypropylene (PP) were prepared in different twin-screw extruders. Two additives, a peroxide initiator and a polymerizable monomer, were added to the polymeric feed components. A large influence on the physical properties, such as toughness and impact strength,. and on the morphology was observed. Reactive extrusion substantially improves mechanical properties: a three-fold increase of elongation at break and doubling of the impact strength. Variation of extruder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…In addition, PE/PS blends were evaluated in terms of the diameter of the dispersed phase, which is an indicator of the effectiveness of the compatibilizers. [17][18][19][20][21] The impact strength is also a good indicator of the effectiveness of the compatibilizers 20 -24 as well as of the processing conditions, [25][26][27] and this was also examined for each blend.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PE/PS blends were evaluated in terms of the diameter of the dispersed phase, which is an indicator of the effectiveness of the compatibilizers. [17][18][19][20][21] The impact strength is also a good indicator of the effectiveness of the compatibilizers 20 -24 as well as of the processing conditions, [25][26][27] and this was also examined for each blend.…”
Section: Introductionmentioning
confidence: 99%
“…b-scission for PP and cross-linking for PE) if the radical sites on the backbone are efficiently transformed to graft sites. [13] The kinetic behavior of this system is complex and do not allow the taking into account of all the parameters in a simple numerical simulation, so some approximations are needed. The aforementioned experimental model compound approach gives rise to two main experimental indicators: (i) the monomer conversion, X MMA ; (ii) the polymerization degree of the PMMA chains, DP n .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast with the pentadecane containing experiment, no agreement between the two sets of data is observed; so we can consider that squalane is not an ideal solution. In the latter case, it is necessary to assume that the activity coefficient of MMA (g) is not equal to one in Raoult's law [Equation (13)]. In a first approximation, we assume that the activity coefficient of MMA is independent of the MMA concentration in the solution.…”
Section: Fitting With Benchmark Datamentioning
confidence: 99%
“…[29,30] Nevertheless, the main drawback of the free radical grafting is the low selectivity of the radical centre, especially at high temperatures (in the range of 150-200 8C, required for the extrusion of PE) leading to side reactions such as coupling and chain scission. [26,31] Using pentadecane as a model for PE and temperatures greater than 160 8C, we showed that the grafting density dramatically decreased because the b-scission reaction of cumyloxyl radicals lead to side reactions. [29] We resorted to pentadecane (C 15 H 32 ) as model for PE because high boiling points of long chain alkanes permit study under high-temperature conditions, typically over 150 8C.…”
Section: Introductionmentioning
confidence: 99%